Optimalisasi Persediaan Bahan Baku Atap Spandex dengan Metode Q - Rizkya, Indah; Fernando (TALENTA Publisher, 2021)
Inventory management is one of the most important aspects in light steel construction business activities. The application of inventory management affects the continuity of the production process and improves the quality of service to consumers. Inventory is defined as an asset which includes goods owned by the company and has the potential to be sold within a certain business period in an effort to meet consumer needs at any time. Galvalume raw material inventory for the spandex roof production process often suffers from shortages due to immature planning. The shortage of inventory causes production not to run smoothly. The purpose of inventory management in this paper is to obtain an inventory policy to optimize the total inventory cost. The method used in this study is economic order quantity. Based on the results and discussion. Ordering raw materials will be made 6 times in a year with an order quantity of 116 with a safety stock of 12 units and will be ordered again when the raw materials are in 46 units. Total Inventory Cost (TIC) which was originally IDR 26.350.191,- can be saved to IDR 21.038.827,- so that the total savings that occurred amounted to IDR 5.311.364,- (20,15%).